(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Customer loyalty is a crucial factor for sustainable business success. To cultivate loyalty, businesses must understand the relationship between customer relationship management (CRM), company reputation, and customer satisfaction. This research paper aims to investigate the direct impact of CRM and company reputation on customer loyalty while exploring the mediating role of customer satisfaction. A mixed-methods approach will be employed, combining both qualitative and quantitative data to provide a comprehensive analysis. The study will draw from existing literature, surveys, and interviews to develop a holistic understanding of the dynamics between CRM, company reputation, customer satisfaction, and customer loyalty. The findings will offer valuable insights to businesses seeking to enhance customer loyalty and optimize their CRM strategies.